The Effect of Green Banking Disclosure and Corporate Social responsibility Disclosure on Firm Value (Study on Islamic Commercial Banks Listed on The Indonesia Stock Exchange) - Utami, Hastin Tri (MALIA: Journal of Islamic Banking and Finance, 2025)
This study aims to examine the effect of Green Banking Disclosure (GBDI) and Corporate Social Responsibility (CSR) Disclosure on firm value at Islamic Commercial Banks listed on the Indonesia Stock Exchange for the period 2018-2022. The data used is secondary data from annual reports and bank sustainability reports, with a sample of three banks selected using purposive sampling method. The number of samples used was 3 samples of Sharia Commercial Bank companies, namely PT Panin Dubai Syariah Bank, PT Bank Syariah Indonesia and PT Bank Tabungan Pensiunan Nasional Syariah. The research method used is multiple linear regression to test the relationship between variables. The results showed that GBDI has a significant negative effect on firm value, while CSR Disclosure, as measured by Islamic Social Reporting (ISR), has a significant positive effect on firm value. Simultaneously, GBDI and CSR Disclosure have a positive influence on firm value. This study concludes that the implementation of green banking needs to be accompanied by strengthening CSR strategies to support sustainability and increase firm value.